Deconstructing Judicial Narratives: Constructivist Analysis of Social and Psychological Framing in a Supreme Court Cassation Decision - Manurung, Rhema Rosa Purnama Esther; Lewoleba, Kayus Kayowuan (Al-Risalah, 2026)
The Supreme Court Decision No. 813 K/Pid/2023, which commuted Ferdy Sambo's death sentence to life imprisonment, sparked controversy and debate regarding the judges' reasoning. This research addresses the analytical gap in previous studies by systematically deconstructing the non-normative foundation of the ruling. Employing normative-juridical research, this study focuses on the qualitative deconstruction of the Supreme Court Decision No. 813 K/Pid/2023 as the primary data, utilizing the constructivist paradigm as the main analytical framework. The novelty of this study lies in its systematic analysis of how the judicial panel actively engaged in judicial narrative construction of the Defendant’s Social and Psychological Experiences. The analysis reveals a dual construction: the defendant was portrayed as a meritorious public servant with long service (social experience), and as an individual whose 'soul was shaken' by emotional provocation (psychological experience). This dualistic construction became the foundation for applying a rehabilitative penal paradigm. The study evaluates that while constructivism effectively unpacks the process of judicial meaning-making, the resulting construction was found to have low normative validity and was imbalanced in considering the victim's interests. This research contributes theoretically to the study of judicial narrative construction and practically to fostering more comprehensive criminal justice practices.